PEMANFAATAN GAMBIR (UNCARIA GAMBIR ROXB) SEBAGAI ANTIOKSIDAN DAN PENGARUHNYA TERHADAP UMUR SIMPAN MINYAK GORENG - Marlina, Popy (Balai Riset dan Standardisasi Industri Palembang, 2010)
The research aimed to obtained gambir optimal cosentration as natural antioxidant and self life cookind oil production. Gambir latex thich was extracted from gambir leaf (Uncaria gambir Roxb) was used in the experiment . the experiment was designedas factorial compeletely randomized design with two factors as treatments, and each combination of gamir antioxidant (1%,2%and 3%), and the second factor was long of storage (7 days,24days,21,days,28day,35days, dand 42days). The result showed that the addition of antioxidant gambir, long of storage and its interaction had significant effect on the peroxide value fat tree acid level and moisture content. The treatment of A2 (gambir consentration 2%) with long of storage 42 days (treatment B6) effective more that gambir consentrations 1%and 3% (treatment A1 and A3) with cooking oil of quality characterstics of 1,6 meq/kg for peroxide value, 0,32% for fatfree aced level , and 0,28% mosture content. The self life of cooking oil by gambir antioxidant is 42 days.